Ontogenetic Migration of Juvenile Grunts (Haemulon) across a Coral Reef Seascape: Pathways and Potential Mechanisms - Richard S. Appeldoorn; Björn L. K. Bouwmeester (Diversity, 2022)
Many coral reef fishes undergo ontogenetic migrations from inshore nurseries to offshore reefs. Quantifying cross-habitat connectivity is important for understanding reef fish spatio-temporal dynamics, essential habitat and spatial planning. Past studies show connectivity is mediated by distance and habitat arrangement. Few studies have documented the pathways linking juveniles and adults, nor suggested underlying orientation/navigation processes important for a more generalized understanding of ontogenetic habitat use. Ontogenetic movements of juvenile grunts, primarily Haemulon flavolineatum, in Puerto Rico were studied using mark-recapture. Small juveniles were tagged at a back-reef site designed to determine their potential movement through a series of size-specific daytime resting schools and posing a choice of direction in migration. Larger juveniles were tagged at mid-shelf reefs to capture off-reef migration to adult locations, including a proposed marine reserve. Small juveniles moved toward more exposed areas, accomplished by progressively shifting locations through existing resting schools. Movement was size-related and alongshore, but direction was primarily parallel to the coast, leading fish away from adjacent areas more directly offshore. Direction may have resulted from the potential mechanism of fish transfer between resting schools rather than by orientation cues. Larger juveniles were tracked from back-reef to fore-reef sites, but no fish were recaptured off-reef. Slower growth than predicted may have contributed to the perceived lack of movement. Localized behavior and habitat distribution appear important in determining the initial pathways of ontogenetic migration, and these may fix later directional movements to unexpected areas.